Pengabdian Masyarakat Sosialisasi Implementasi Sistem Pemilu Indonesia di Bawaslu Jakarta Pusat - Suhariyanto, Didik (Jurnal Pengabdian Masyarakat Singa Podium (JPMSIPO), 2024)
General elections in Indonesia are a democratic mechanism to determine leaders who are expected to have legitimacy, namely recognition and support from the voting public at large. To achieve this, Indonesia needs an electoral system that is effective and in accordance with the country's conditions. Elections in this country have been regulated through the 1945 Constitution and are conducted through direct and representative election methods. There were variations in the electoral system before and after the 1945 constitutional amendment was made. This electoral system is set up to ensure that the voting process is conducted directly, publicly, freely, confidentially, honestly, and fairly. However, the implementation of the current electoral system shows some shortcomings that require improvement to ensure better elections in the future.